1996
DOI: 10.2134/jpa1996.0554
|View full text |Cite
|
Sign up to set email alerts
|

Net Returns from No-Till Doublecrop Winter Wheat and Irrigated Soybean on a Clay Soil

Abstract: Economic evaluation of agronomic production practices is required to determine their feasibility in cropping systems with two or more crops. Net returns from continuous double‐cropped wheat (Triticum oestivum L.) and irrigated soybean [Glycine ma (L.) Merr.] were calculated using data from plantings made in 1988, 1989, and 1990 near Stoneville, MS, on a Tunica clay (clayey over loamy, montmorillonitic, nonacid, thermic, Vertic Haplaquept) in tilled and no‐till seedbeds in both burned and standing wheat stubble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Wheat yield ranged from 4838 to 5497 kg ha −1 (Table 2), with a 3‐yr average of 5170 kg ha −1 This was much higher than the county's (Washington County) average yield of 3462 kg ha −1 for 2000 through 2004 (Mississippi Agricultural Statistics Service, 2005c) and those reported previously for the same location but a different site in Mississippi (Wesley and Cooke, 1988; Heatherly et al, 1996). Wesley and Cooke (1988) reported an average yield of 3233 kg ha −1 , whereas Heatherly et al (1996) indicated 2930 kg ha −1 for their 1988 experiment. The differences in yield are likely related to differences in varieties, soil type, and rainfall pattern between this study and earlier studies.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Wheat yield ranged from 4838 to 5497 kg ha −1 (Table 2), with a 3‐yr average of 5170 kg ha −1 This was much higher than the county's (Washington County) average yield of 3462 kg ha −1 for 2000 through 2004 (Mississippi Agricultural Statistics Service, 2005c) and those reported previously for the same location but a different site in Mississippi (Wesley and Cooke, 1988; Heatherly et al, 1996). Wesley and Cooke (1988) reported an average yield of 3233 kg ha −1 , whereas Heatherly et al (1996) indicated 2930 kg ha −1 for their 1988 experiment. The differences in yield are likely related to differences in varieties, soil type, and rainfall pattern between this study and earlier studies.…”
Section: Resultsmentioning
confidence: 66%
“…This was not the case in 2004; perhaps the short growing season favored the MG III cultivars relative to the late MG IV cultivars (Table 3). The results from this 3‐yr study and those from Wesley and Cooke (1988) and Heatherly et al (1996) indicate that MG V and VI cultivars may not have a yield advantage over MG IV and III cultivars when planted in a double‐crop system and could be a risk if planted after early June in a season with terminal wet conditions. Yields at the same location (Stoneville) in Mississippi and under similar production practices for double‐cropped MG VI averaged 2331 kg ha −1 (Wesley and Cooke, 1988), whereas yields for MG V averaged 2641 kg ha −1 (Heatherly et al, 1996).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…We observed no change in yield of wheat could be attributed to including wheat in a rotation with soybean. In contrast, Heatherly et al (9) reported low and declining wheat yields in a three‐year study of continuous wheat‐soybean doublecropping using no‐till wheat planting. Higher wheat yields have been reported for monocrop compared to wheat‐soybean doublecropping (8).…”
Section: Experiment Results and Findingsmentioning
confidence: 92%
“…Early-season soybean can be followed by planting winter wheat as a doublecrop (1,10). Alternatively, in winter wheat production regions with adequate frost-free periods and rainfall, such as the southern USA, double cropping soybean following wheat is possible (8,9,17,19). Limited summer rainfall is not conducive to successful doublecropping, particularly with respect to soybean following wheat.…”
Section: Introductionmentioning
confidence: 99%